Availability and use of in-patient electronic health records in low resource setting. (October 2018) - Qazi, Umair; Haq, Mahdi; Rashad, Nabhan; Rashid, Khalid; Ullah, Shahid; Raza, Usman
Highlights: Adoption of Electronic Health Records (EHR) is an emerging challenge in developing countries but not yet documented in Pakistan. This study evaluates the availability and use of in-patient EHR systems in Peshawar, Pakistan. We categorized the hospitals into small (<100), medium (100–500) and large (>500) by bed-count and EHR (basic and fully-functional) on computer system capabilities. Out of 58 hospitals, 35 were randomly selected. A pre-tested data collection tool was used. Only 1 hospital met the requirements of basic EHR, and none qualified for fully functional EHR. However, 9/35 hospitals (26%) had at least one EHR feature. Top reported hurdles in EHR use were high cost (46%), doubt about usefulness (19%), and doctors' unwillingness to use (19%). This is the first report on EHR availability in Pakistan, results may serve as a bench mark for improvement. By highlighting the need for EHR adoption, resources may be allocated to develop a national strategy to support the adoption and use of EHR.